2020
DOI: 10.1145/3377343
|View full text |Cite
|
Sign up to set email alerts
|

The Robot Makers

Abstract: This article is an ethnographic exploration of robot anthropomorphism at a robotics company. It draws on a 10-month participatory ethnography among a robotics company, an anthropologist, and a social robotics research lab. In contrast to psychological methods, this anthropological participatory ethnography integrates all stakeholders' insights, offering holistic understandings of robots' in situ operations throughout the fieldwork, data-sharing, interviews, and analysis. In particular, this article unravels em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(6 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…AIS are often designed to have human-like features to please humans and a stream of research in social robotic and HCI is concerned with optimising these qualities to improve perceived interactional meaningfulness, trust, and connectedness [38,39]. In relationship to human behaviour, anthropomorphism is 'the tendency to imbue the behaviour of nonhuman agents with human-like characteristics' [40, p.864].…”
Section: Genai and The Challenge Of Anthropomorphismmentioning
confidence: 99%
See 1 more Smart Citation
“…AIS are often designed to have human-like features to please humans and a stream of research in social robotic and HCI is concerned with optimising these qualities to improve perceived interactional meaningfulness, trust, and connectedness [38,39]. In relationship to human behaviour, anthropomorphism is 'the tendency to imbue the behaviour of nonhuman agents with human-like characteristics' [40, p.864].…”
Section: Genai and The Challenge Of Anthropomorphismmentioning
confidence: 99%
“…In research, participants may be unwilling to acknowledge the extent to which they anthropomorphise. For instance, in a study of robot makers by Chun and Knight [38], they found that anthropomorphism was strongly evident in interviews describing participants' experiences of the robots but was frequently disavowed. In this paper, we not only acknowledge our tendencies to anthropomorphise AI, but we also examine how these tendencies and perceptions influences our subjectivity and relationship with AI.…”
Section: Genai and The Challenge Of Anthropomorphismmentioning
confidence: 99%
“…Previous work on robot teams explored the attitudes of frontline employees who use industrial robots every day ( Sauppé and Mutlu, 2015 ; Elprama et al, 2017 ; Wurhofer et al, 2018 ; Welfare et al, 2019 ). Additionally, an extensive ethnographic investigation studied anthropomorphism in teams that work with robots ( Chun and Knight, 2020 ). While these studies focus on the team that directly works side-by-side with robots, our work focuses on the experience of teams that design and build new robots.…”
Section: Related Workmentioning
confidence: 99%
“…2016; used with permission). Panel B: An anthropologist at a robotics company in North America, where she visited for three weeks collecting ethnographic data (© Chun and Knight 2020; used with permission). Panel C: An anthropologist planting rice at their fieldsite (© Liana Chua; used with permission).…”
Section: Introductionmentioning
confidence: 99%